(untitled) (Journal of The Colloquium for Information Systems Security Education, 2019)
Since 2012, the National Integrated Cyber Education Research Center has existed with the express goal of supporting local workforce development in the areas of STEM, cyber, and computer science. In that time, a variety of subject matter experts have contributed to writing content that is now in use by more than 8,000 teachers across the country. In addition to providing that content to United States public school teachers at no cost, the organization and subject matter experts also provide free professional development to ensure that teachers are as prepared as possible when they present this content in their classrooms. Lastly, the organization also provides opportunities for extracurricular engagement by students outside of the traditional classroom model. Content for events such as robotics competitions, science fairs, and maker spaces are also provided by the organization. This paper will investigate a variety of research studies that support the organization’s mission as well as particular studies that identify the organization’s offerings as a critical need to education in the 21st century.